Osebnostne značilnosti sorojencev in tipi njihovega medosebnega odnosa v otroštvu - Kavčič, Tina (Psihološka obzorja (Ljubljana), 2010)
The contribution presents a follow-up study of sibling relationship and personality in 87 sibling dyads in early/middle childhood from parental perspective. At Time 1 all siblings attended pre-school and one year later approximately half of the older siblings entered compulsory school. At both times of measurement siblings' mothers and fathers independently reported on their children's personality characteristics using the Inventory of Child Individual Differences (Halverson et al., 2003; Slovene adaptation, Zupančič & Kavčič, 2009) and on the observed sibling warmth, agonism, and rivalry using the Parental Expectations and Perceptions of Children's Sibling Relationships Questionnaire (Kramer, 2001). The predictive relationship obtained by two sets of cross-rater analyses (between maternal ratings of child personality and paternal reports on sibling relationship, and vice versa) suggested that (a) personality traits of both siblings and (b) the match between siblings' personalities are associated with sibling type (affectionate, involved or average) membership. Among personality traits, disagreeableness seems to be an especially significant contributor to sibling relationship quality.
Keywords: sorojenci; medosebni odnosi; otroštvo; osebnostne lastnosti